Measurements of 18O‐Pi uptake indicate fast metabolism of phosphate in tree roots. (25th January 2019) - Scheerer, U.; Netzer, F.; Bauer, A. F.; Herschbach, C.
Abstract: Phosphorus (P) nutrition of beech ecosystems depends on soil processes, plant internal P cycling and P acquisition. P uptake of trees in the field is currently not validated due to the lack of an experimental approach applicable in natural forests. Application of radiolabelled tracers such as 33 P and 32 P is limited to special research sites and not allowed in natural environments. Moreover, only one stable isotope of P, namely 31 P, exists. One alternative tool to measure P acquisition in the field could be the use of 18 O‐labelled 31 P‐phosphate ( 31 P 18 O4 3− ). Phosphate (Pi ) uptake rates calculated from the 18 O enrichment of dried root material after application of 31 Pi 18 O4 3− via nutrient solution was always lower compared to 33 P incorporation, did not show increasing rates of Pi uptake at P deficiency under controlled conditions, and did not reveal seasonal fluctuations in the field. Consequently, a clear correlation between 33 P‐based and 18 O‐based Pi uptake by roots could not be established. Comparison of Pi uptake rates achieved from 33 P‐Pi and 18 O‐Pi application led to the conclusion of high Pi metabolism in roots after Pi uptake. The replacement of 18 O by 16 O from water in 18 O‐Pi during root influx, but most probably after Pi uptake into roots, due to metabolic activities, indicates high and fast turnover of Pi . Hence, the use of 18 O‐Pi as an alternative tool to estimate Pi acquisition of trees in the field must consider the increase of 18 O abundance in root water that was disregarded in dried root material.